2024
DOI: 10.1039/d3nr05348b
|View full text |Cite
|
Sign up to set email alerts
|

The controllable and efficient synthesis of two-dimensional metal–organic framework nanosheets for heterogeneous catalysis

Ling-Xia Yun,
Cong Zhang,
Xin-Ran Shi
et al.

Abstract: 2D MOF nanosheets prepared using a high-gravity reactive precipitation method exhibit high catalytic activities toward Knoevenagel condensation and the glycolysis of poly(ethylene terephthalate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Recently, Yun et al showed that two-dimensional (2D) MOFs nanosheets obtained by using high-gravity RPB (ZIF-L-RPB), presented excellent heterogeneous catalytic activity for the glycolysis of poly(ethylene terephthalate) (PET) compared to nanosheets prepared in a stirred tank reactor (ZIF-L-STR) [ 190 ]. As a result, PET was degraded with a conversion rate of 99.4%, and the yielded BHET was 93.9% within a 30-min period, utilizing only a minimal amount of 0.2 wt.% at 195 °C [ 190 ]. These findings suggest that MOFs can offer encouraging potential for being used as cost-effective heterogeneous catalytic applications.…”
Section: Oxide-based Catalystsmentioning
confidence: 99%
“…Recently, Yun et al showed that two-dimensional (2D) MOFs nanosheets obtained by using high-gravity RPB (ZIF-L-RPB), presented excellent heterogeneous catalytic activity for the glycolysis of poly(ethylene terephthalate) (PET) compared to nanosheets prepared in a stirred tank reactor (ZIF-L-STR) [ 190 ]. As a result, PET was degraded with a conversion rate of 99.4%, and the yielded BHET was 93.9% within a 30-min period, utilizing only a minimal amount of 0.2 wt.% at 195 °C [ 190 ]. These findings suggest that MOFs can offer encouraging potential for being used as cost-effective heterogeneous catalytic applications.…”
Section: Oxide-based Catalystsmentioning
confidence: 99%
“…4 Metal−organic framework (MOF) crystalline materials have good optical properties due to their unique characteristics of diverse structure, large specific surface area, tunable pore size, and abundant active sites on the pore surface that are easy to be functionalized. 5,6 They have potential applications in gas separation and adsorption, 7 heterogeneous catalysis, 8 biological imaging, 9 drug delivery, 10 and fluorescence sensing. 11,12 In general, the variable metal centers and organic ligands of MOF materials result in structural and functional diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The current research has yielded a diverse range of materials , for the adsorption and detection of environmental pollutants, with fluorescence sensing materials being highly favored due to their exceptional attributes of superior selectivity and ultralow detection limits . Metal–organic framework (MOF) crystalline materials have good optical properties due to their unique characteristics of diverse structure, large specific surface area, tunable pore size, and abundant active sites on the pore surface that are easy to be functionalized. , They have potential applications in gas separation and adsorption, heterogeneous catalysis, biological imaging, drug delivery, and fluorescence sensing. , In general, the variable metal centers and organic ligands of MOF materials result in structural and functional diversity. Compared with the commonly used transition metal center elements, rare earth elements are more susceptible to sensitization effects during the transfer process due to their unique 4f-orbital electrons in lanthanide metal–organic frameworks (Ln-MOFs) and can lead to an increase in their Stokes shifts and higher quantum yields .…”
Section: Introductionmentioning
confidence: 99%